THE DEGRADATION OF THE PROTECTIVE SCALE ON BINARY FeCr ALLOYS (Fe-2.25Cr, Fe-10Cr, Fe-18Cr AND Fe-25Cr) IN CO2 AND IN CO2 + H2O ENVIRONMENT AT 600oC - Bagas Pujilaksono (Testing Center for Oil and Gas LEMIGAS, 2016)
The oxidation behaviour of the binary alloys Fe-2.25, Fe-10Cr, Fe-18Cr and Fe-25Cr in dry and wet O2 at 600oC is investigated by isothermal exposures of carefully polished samples for up to 168 hours. The oxidized samples are investigated gravimetrically and the oxides formed are studied by X-ray diffraction. X-ray photoelectron spectroscopy is used for depth pro􀂿 ling of the thin oxides. The scale surface is imaged by SEM. Cross sections through the scale are analyzed by SEM/EDX for imaging and for measuring the chemical composition. The oxidation behavior of the four FeCr alloys is intermediate between those of iron and chromium. Fe-2.25Cr oxidizes in a way similar to iron in both environments, forming a poorly protective scale consisting of FeCr spinel at the bottom, magnetite in the middle and a hematite cap layer. In dry O2, Fe-10Cr, Fe-18Cr and Fe-25Cr form a thin and protective (Fe,Cr)2O3 oxide similar to the chromia 􀂿 lm formed on pure chromium. In wet O2, Fe-10Cr, Fe-18Cr and Fe-25Cr initially form the same kind of protective oxide 􀂿 lm as in dry conditions. After an incubation time that depends on alloy chromium content, all three alloys go into breakaway oxidation and form thick, poorly protective scales similar to those formed on Fe-2.25Cr. Breakaway oxidation in wet O2 is triggered by the evaporation of CrO2(OH)2 from the protective (Fe,Cr)2O3 oxide.